In vitro antiviral activity of Brazilian Cerrado plant extracts against animal and human herpesviruses - Marina A. Padilla, Isabela C. Simoni, Verônica Moreira H. Hoe , Maria Judite B. Fernandes , Clarice W. Arns , Juliana R. Brito , João Henrique G. Lago (African Journal of Pig Farming, 2023)
The Brazilian savanna known as “Cerrado” is very rich in medicinal plants that are used by the local population for treatment of several illnesses. The herpesvirus is a serious problem worldwide, and affects both animal and human health. This work aimed to study the antiviral activity of eight extracts from plants natives of “Cerrado” region against human (HSV-1), equine (EqHV-1) and swine herpesviruses (SuHV-1). The results showed that all plant extracts: Banisteriopsis variabilis, Byrsonima intermedia, Campomanesia xanthocarpa, Erythroxilum deciduum, Lacistema hasslerianum, Ocotea pulchella, Stryphodendron adstringens and Xylopia aromatica presented antiviral activity against at least one herpesvirus. Furthermore, it was observed a direct anti-herpes effect of extracts from B. variabilis and B. intermedia in non-toxic concentrations against all herpesviruses. B. intermedia crude aqueous extract showed the most promising results with selective index values of the 41.76 ± 0.04; 4.12 ± 0.1 and 193.97 ± 0.09 respectively against HSV-1, EqHV-1 and SuHV-1. Due to this, B. intermedia extract was also analyzed by HPLC/MS allowing for the identification of gallic acid and quercetin as main compounds.